Proses Penyidikan Terhadap Pelaku Tindak Pidana Pencurian Disertai Kekerasan Studi Kasus di Polres Agam - Mahesa Pandu Erlangga; Sukmareni Sukmareni; Syaiful Munandar (LPPM Universitas Ekasakti Padang, 2023)
Investigation is the stage of resolving a criminal case after an investigation, which is the initial stage of looking for the presence or absence of a criminal offense in an event. When it is known that a criminal offense has occurred, then that is when an investigation can be carried out based on the results of the investigation. In the act of investigation, the emphasis is placed on the act of searching and finding an event suspected of being a criminal act. Whereas in the investigation, the emphasis is placed on the act of searching and collecting evidence. Investigation aims to make light of the criminal offense found and also determine the perpetrator. This research is descriptive, which is research that aims to provide data that is as accurate as possible about the circumstances that are the object of research in this case about the investigation process against the perpetrators of the crime of gold robbery in the Agam Police area, so as to find answers to problems in the implementation of the investigation of criminal acts of theft accompanied by violence which was first carried out after receiving a report from the victim, namely processing the crime scene, asking for witness and victim testimony, after finding some preliminary evidence, several forced measures were taken, namely the arrest of the perpetrator, detention, and also confiscation. Investigations carried out by investigators play a role in uncovering or resolving a criminal offense. Therefore, investigators must improve their performance, so that they can complete the shortcomings in the investigation and can also overcome the obstacles that occur in the implementation of criminal investigations.